EFEKTIVITAS CACING TANAH (Lumbricus rubellus) SEBAGAI AGEN BIOREMEDIASI TANAH TERCEMAR OLI MESIN DI KOTA MEDAN - Indriani, Pramita; Erisa Rizki Lubis, Putri; Diana Citra, Umi; Misella, Naomi; Nilan Sari Rangkuti, Marlinda; Febriyossa, Adelia (Universitas Cokroaminoto Palopo, 2024)
Soil contamination due to the disposal of used oil that has not been managed properly in automotive workshops has the potential to cause pollution and environmental damage. One alternative treatment that can be done is bioremediation using earthworms as bioremediation agents. This study aims to determine the effectiveness of earthworms in accelerating the recovery of soil contaminated with engine oil and the factors that influence the effectiveness of earthworms as bioremediation agents in soil contaminated with engine oil. The method used is an experiment with different treatment variations in each media. This study was conducted by mixing soil contaminated with engine oil, vermicompost, and earthworms. The test results showed that earthworms were able to reduce the levels of hydrocarbon compounds in the soil for 21 days of observation.accomplished with the aid of digital devices.